Dissemination of Politeness in Directive Speech Acts on the Medical Records Officer in the Admissions Section at Rs. TkIII Dr. Reksodiwiryo Padang - mayasari, Nila (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Language as a very important role in everyday life cannot be separated from human life. In various language activities humans use to interact with other humans in each of their activities. The activities in question are all human daily activities from waking up to going back to sleep, for example when chatting with family, going to school, playing and at work. Mastering speech techniques is one of the supporting aspects that must be owned by a medical recorder of health information (PMIK). especially by the medical recorder in charge of the admissions section, because the admissions section is the first source of data that is recorded when a patient arrives. This Community Service (PKM) aims to improve the ability to use polite speech in good language for medical record officers, especially admissions section.